Antifertility effect of hydroalcoholic extract ofPandanus odoratissimusL. leaves. Issue 5 (September 2017) - Kumar, Satyender; Dagar, Seema; Kumar, Pushpander; Singh, Jitender; Kumar, Sunil; Kumar, Dinesh
Abstract : Abstract : This study was undertaken to assess the antifertility effect of hydroalcoholic leaves extract of Pandanus odoratissimus Linn. which is traditionally used by the woman in Rajasthan state of India to regulate the fertility. The antifertility activity of the extract at dose levels (200 and 400 mg/kg, orally) was evaluated in two experimental animal models. The extract was found to be safe up to a dose of 4000 mg/kg of the extract when administered orally. A good antiimplantation (37.13%) activity in female rats was observed at the tested dose level (400 mg/kg). The extract, when administered alone at 200 mg/kg dose to immature female albino rats, enhanced the estrogen level in the serum whereas significantly decreased the estrogen level at 400 mg/kg dose. The extract along with estradiol at dose level of 400 mg/kg significantly ( p < 0.01) decreased the level of estrogen, in comparison to standard group rats indicating the antiestrogenic nature of the extract. The antiestrogenic effect of the extract at higher dose (400 mg/kg) might be due to negative feed‐back inhibition on anterior pituitary. Preliminary phytochemical screening has revealed the presence of alkaloids, carbohydrates, flavonoids and saponins in the hydroalcoholic leaf extract of the plant. The antifertility effect of the plant might be due to antiimplantation as well as antiestrogenic effect of the extract which in turn might be due to some of the chemical constituents present in the extract. The results shows that hydroalcoholic extract of P. odoratissimus L. leaves possess significant antifertility activity at 400 mg/kg, thus, justifying the traditional use of this plant in fertility regulation in females.